Mauritania and the European regional system of post-colonialism to Euro-Mediterranean Association - Juan Manuel Uruburu Colsa (Revista CIDOB d'Afers Internacionals, 2010)
During the five decades that have elapsed since it gained independence, Mauritania – a country that is lacking in natural resources and highly dependent on exterior aid – has prioritised its relations with the European regional system. These relations have been a reflection of the evolution of the principles of EU external action. Thus, during the period prior to the Maastricht Treaty, relations with Mauritania were framed within a collection of agreements based on development cooperation and fishing licences. However, with the introduction (in the 1990s) of a European Common Foreign and Security Policy, provided with new principles, a new political dimension was introduced into these relations; a dimension that would demonstrate its importance in Mauritania’s recent political evolution. In this context, the aim of this article is: to analyse the main elements that have determined the evolution of this process of relations between the European Union and Mauritania; to examine the effects of the introduction of political criteria into this cooperation, and its impact on Mauritania’s increasing closeness to the Euro-Mediterranean space; and to highlight, particularly, Spain’s role with respect to designing EU strategies in areas of particular importance for our country’s interests, such as political dialogue, controlling migration flows and fishing.